The geopolitical importance of the Hanish Islands and their impact on international navigation security - Kaittan, Wisam Ali (Al-Adab Journal, 2021)
This research has dealt with the geopolitical importance of the islands of the Hanish archipelago located at the southern entrance to the Red Sea and close to the Bab al-Mandab Strait, which has geopolitical, economic and military importance and is considered one of the large islands in the region after Zuqar Island and is empty of population due to its geographical nature represented in its volcanic formation and lack of The water is safe to drink and has rugged terrain, but its importance lies in its island position, which overlooks the entrance to the Gulf of Aden and the southern gate of the Red Sea. Locality, the islands have economic importance, as they contain many minerals, the most important of which is oil and gas. Therefore, they have become the focus of attention for regional and international strategic competition. Three topics preceded by an introduction and a theoretical framework were presented in the research. The first topic dealt with the geographical location of the islands and their importance at the geopolitical, economic and military level, while the second topic It dealt with regional and international strategies towards the islands and the geopolitical effects A yakiya for the islands on the Red Sea, the Bab al-Mandab strait, and the Horn of Africa. As for the third topic, it dealt with future scenarios for the Hanish islands, and concluded the research with the most important conclusions.